Lecture10 Cai
Lecture10 Cai
Lecture10 Cai
(Lecture 10)
a b (addition/subtraction), ab (multiplication).
a b (addition/subtraction), ab (multiplication).
b/a = b a1 ,
a b (addition/subtraction), ab (multiplication).
b/a = b a1 ,
Definition
The identity matrix of order n is given by the following n n
matrix:
1 0 0
0 1
0
0 0 0
0 0 1
Definition
Let M be a square matrix of order n (i.e., n n matrix) and I be
the identity matrix of order n. If there exists a matrix N such that
NM = MN = I ,
Remark
I Conventionally, the inverse of M is denoted by M 1 .
I M 1 is of the same size as M.
I M 1 may not exist.
I If N is a square matrix of the same order of M and MN = I ,
then one can show that NM = I .
Example
2 3
Find the inverse of M = .
1 2
Example
2 3
Find the inverse of M = .
1 2
a c
Solution: we look for M 1 = such that
b d
MM 1 = M 1 M = I .
We have
2 3 a c 1 0
= .
1 2 b d 0 1
Therefore
( (
2a + 3b =1 2c + 3d =0
,
a + 2b = 0, c + 2d = 1,
The solution is
a 2 c 3
= =
b 1 d 2
2 3
Thus, the inverse of the matrix M = is
1 2
1 2 3
M = .
1 2
Recall the augmented matrices in the steps for finding the inverse
of the matrix M in the previous example:
2 3 1 2 3 0
, .
1 2 0 1 2 1
The left sides of augmented matrices are the same: the matrix M.
Thus, exactly the same row operations can be used on each
augmented matrix to transform it into the reduced form. We can
transform all the augmented matrices simultaneously by combining
all two augmented matrices into a single augmented matrices of
the following form:
2 3 1 0
= [M|I ].
1 2 0 1
we obtain,
1 0 a c
= [I |M 1 ].
0 1 b d
Theorem
Let M be an n n matrix and I be the n n identity matrix. If
(M|I ) can be transformed by row operation(s) into (I |B), then the
resulting matrix B is the inverse of M, that is M 1 = B.
Row operations
(M|I ) (I |M 1 ).
Example
Find the inverse of each of the following matrices
5 2 2
(a) 2 1 0
1 0 1
2 1 1
(b) 1 1 0 .
1 1 0
0 0 1 1 2 1
1 0 1 0 0 1 R2 +2R3 R2 1 0 0 1 2 2
R1 +(1)R3 R1
0 1 2 0 1 2 0 1 0 2 3 4
0 0 1 1 2 1 0 0 1 1 2 1
1 2 2
Therefore, 2 3 4 is the inverse of
1 2 1
5 2 2
2 1 0 .
1 0 1
2 1 1 1 0 0 1 1 0 0 0 1
1 R3
1 1 0 0 1 0 R 1 1 0 0 1 0
1 1 0 0 0 1 2 1 1 1 0 0
R2 +(1)R1 R2 1 1 0 0 0 1
R3 +(2)R1 R3
0 0 0 0 1 1
0 1 1 1 0 2
Theorem
a b 1 1 d b
When M = , then M = where
c d D c a
D = ad bc, provided that D 6= 0.
Remark
D is called the determinant of M.
Example
2 3
Find the inverse of .
1 1
Solution
By definition, D = 2 1 1 3 = 1 6= 0. By the previous
theoerem, we have
1
2 3 1 1 3
=
1 1 1 1 2
1 3
=
1 2